Tópicos cénicos e inversão locativa: Os casos do inglês, francês e português europeu - Joana Teixeira (Revista da Associação Portuguesa de Linguística, 2016)
This paper seeks to show that languages with distinct degrees of word order flexibility, like English, French and European Portuguese (EP), only permit locative inversion (LI) with preverbal XPs which are stage topics. This is argued to be both a necessary and sufficient condition for an XP to be admitted in LI. In addition to the structures typically classified as LI, “absolute inversion” in French, “free” inversion in wide-focus contexts in EP, and inversion structures with participial and adjectival phrases in English and French are argued to be licensed by (c)overt stage topics and, thus, constitute forms of (covert) LI.